Evaluating The Effectiveness Of Delivery Standard Operating Procedures (Sops): A Case Study At PT Tustika Nagata (2025) - Maria Anjelina Margaretha Pajo; Muazaroh Muazaroh (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to evaluate the effectiveness of the Standard Operating Procedures (SOP) for goods delivery at PT Tustika Nagata, a logistics company based in Surabaya, Indonesia. Employing a qualitative descriptive approach, the research utilized data collection techniques including interviews, field observations, and documentation review. Findings indicate that the current SOP implementation still faces challenges such as late submission of delivery notes, delayed vehicle returns, discrepancies in spare part expense reporting, and inadequate vehicle maintenance by drivers. Internal constraints include a lack of discipline among operational staff and insufficient SOP enforcement, while external factors involve limited integration of technology in logistics processes. The study emphasizes the importance of well- structured SOPs in improving administrative accuracy, vehicle rotation efficiency, and financial accountability. Based on the analysis, recommendations include enhancing employee discipline, refining SOP content, digitizing logistics workflows, and providing routine training. These improvements are expected to increase the operational efficiency and reliability of PT Tustika Nagata’s delivery system in supporting seamless logistics performance.